1958
DOI: 10.1007/bf01342879
|View full text |Cite
|
Sign up to set email alerts
|

�ber die Temperaturabh�ngigkeit der spektralen lichtelektrischen Elektronenemission halbleitender Wismutfilme

Abstract: i3ber die Temperaturabh/ingigkeit der spektralen lichtelektrischen Elektronenemission halbleitender Wismutfilme* Won R. SUHRMANN, G. WEDLER und E.-A. DIERK Mit 8 Figuren im Text (Eingegangen arn g. Juli 1958) Es wird die spektrale photoelektrische Empfindlichkeit dfinner im Hochvakuum aufgedampfter Filme aus reinem und aus mit Tellur dotiertem Wismut im ungeordneten und geordneten Zustand gemessen. --Die Auswertung der nach Fow-LER aufgetragenen Empfindlichkeitskurven ergibt folgendes : Das Austrittspotential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

1959
1959
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…This interaction has been extensively studied as an example of activated adsorption. The early work of Kemball 1 and Suhrmann et al 2 indicated that the activation energy was in the range 310 to 420 meV. There is now a general consensus from a series of molecular beam studies that it is a direct activated process.…”
Section: Introductionmentioning
confidence: 99%
“…This interaction has been extensively studied as an example of activated adsorption. The early work of Kemball 1 and Suhrmann et al 2 indicated that the activation energy was in the range 310 to 420 meV. There is now a general consensus from a series of molecular beam studies that it is a direct activated process.…”
Section: Introductionmentioning
confidence: 99%
“…Early work [1,2] indicated an activation energy in the range of 310 to 420 meV. A consensus appears to be emerging from a series of molecular beam studies that this is a direct activated process [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
mentioning
confidence: 99%
“…In one type, the plot of log lObs against v fits th( theoretical Fowler curve (Fowler 1931) ; in other cases, however, a curve is obtained which is in two parts, each of which can be fitted to a separate Fowler curvc. Thus Suhrmann, Wedler, andDierk (1958a, 1958b) obtained " composite" curves from bismuth films, and we have found both types of behaviour with evaporated nickel films undergoing stepwise oxidation. The problem of interpreting such composite curves is quite a general one.…”
mentioning
confidence: 79%